Criminal Legal Regulation of Trafficking in Human Bodies: Spanish and Brazilian Experience - V. Shestak; A. Tsyplakova (BRICS Law Journal)
Organ trafficking, a very profitable worldwide illegal activity today, is frequently overlooked by those involved in combating human trafficking due to its complex and covert nature. Numerous international documents underscore the importance of countering trafficking in human organs and transplant tourism. This article analyzes the legal frameworks of Spain and Brazil, with a particular focus on their compliance with international and supranational standards aimed at combating, inter alia, the illegal circulation of organs and other phenomena associated with it. Firstly, the article distinguishes such phenomena as transplant commercialism, transplant tourism and illegal trafficking in organs and draws attention to the fact that currently there is no uniform understanding of the clear boundaries of the concept of illegal trafficking in organs. Elaborating on the various aspects of the above-mentioned types of criminal activity may allow one to properly determine the legal interests and rights protected by criminal law and the types of behavior subject to imputation in an exhaustive way. Secondly, the authors outline a number of controversial issues that arise due to the complex nature of organ trafficking and suggest several ways to meet these challenges.